STUDI KEANEKARAGAMAN MAKROZOOBENTOS DI SUNGAI BAH BIAK KOTA PEMATANGSIANTAR PROVINSI SUMATERA UTARA - Frans Wilis Siregar; Ewin Handoco S; Mardame Pangihutan Sinaga (Journal of Research and Publication Innovation, 2025)
Macrozoobenthos is a group of organisms that live in or on the surface of the bottom sediment of waters and have a length of more than 1mm. One of the habitats of macrozoobenthos is the freshwater ecosystem in the Bah Biak River, Pematangsiantar City, North Sumatra Province. It is known that macrozoobenthos can provide food availability for other organisms and as an indication of the suitability of the potential quality of waters, especially pollution indicators and play an important role in the decomposition process of organic matter in sediments in freshwater ecosystems so that the macrozoobenthos community can be used as an indicator of the balance of aquatic ecosystems. This study aims to; To identify the diversity, uniformity and dominance of Macrozoobenthos in the Bah Biak River area, Pematangsiantar City, North Sumatra Province. This study used a combination of two transect methods, namely line transects and quadrat transects. Determination of the research location using purposive sampling techniques. Data analysis using qualitative and quantitative analysis. The results of the study showed that there were 4 species of Macrozoobenthos consisting of 2 classes with a total of 95 individuals. The diversity of Macrozoobenthos in the Bah Biak River, Pematangsiantar City, North Sumatra Province is classified as moderate with a diversity index of H’ = 1.27 – 1.35, the evenness index is classified as stable ranging from 0.92 – 0.97 and the dominance index is classified as high.